Individual cumulative match loads in the LIQUI MOLY Handball Bundesliga over an entire season - Baumgart, C.; Hoppe, M. W.; Saal, C. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: For training control and injury prevention, knowledge of the individual match loads is essential. However, in elite handball, these loads have not been adequately described using quantitative measurements. The aim of this study was to quantify the cumulative match loads in the LIQUI MOLY Handball Bundesliga (HBL) over an entire season. METHODS: The match loads of two men`s handball teams were recorded during each competitive match of the season 2021/2022 (a total of 66 matches) using a validated radio-based positioning system (Kinexon Perform LPS, Kinexon GmbH, Munich). Match loads were operationalized based on the number of completed matches, playing time, total distance covered as well as the number of sprints, jumps, shots on goal, passes, and impacts. For validity reasons, only players with at least six match appearances (a total of 30 players) were considered. Quantiles of cumulative match loads (Q) were used for statistical analysis. RESULTS: On average (Q50), 27.5 matches are played per season (Q0 = 9; Q25 = 20; Q75 = 30; Q100 = 32), corresponding to an average cumulative playing time (Q50) of 12 hours (Q0 = 1; Q25 = 7; Q75 = 19; Q100 = 26). The average cumulative values over the entire season are as follows: • Total distance covered: Q50 = 56.9 km (Q0 = 4.9; Q25 = 35.1; Q75 = 90.3; Q100 = 134.5) • Number of sprints: Q50 = 77 (Q0 = 8; Q25 = 47; Q75 = 150; Q100 = 912) • Jumps: Q50 = 256 (Q0 = 10; Q25 = 120; Q75 = 393; Q100 = 960) • Shots on goal: Q50 = 107 (Q0 = 6; Q25 = 49; Q75 = 148; Q100 = 244) • Passes: Q50 = 1,137 (Q0 = 74; Q25 = 512; Q75 = 2,360; Q100 = 5,319) • Impacts: Q50 = 216 (Q0 = 10; Q25 = 69; Q75 = 399; Q100 = 519) CONCLUSION: The cumulative match loads in the HBL demonstrate significant inter-individual variation. In both teams, there are some players who suffer very high loads at the end of the season. These results can be attributed, among other factors, to the varying demands of different playing positions and the effective playing time of regular players. Further studies are necessary to transfer these findings into the practice of elite handball.